2003
DOI: 10.1016/s0168-6496(03)00149-1
|View full text |Cite
|
Sign up to set email alerts
|

Salinity as a structuring factor for the composition and performance of bacterioplankton degrading riverine DOC

Abstract: The impact of salinity on the composition and functional performance (biomass production, growth efficiency and growth rates) of bacterial communities was investigated using batch cultures growing on dissolved organic carbon from a river draining into the Northern Baltic Sea. The cultures were adjusted to riverine or estuarine salinity levels and inoculated with bacteria from these two environments. Bacterial growth efficiencies differed in response to salinity and the origin of the inoculum. When salinity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
86
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(94 citation statements)
references
References 60 publications
8
86
0
Order By: Relevance
“…Previous studies in the Arctic underscore the importance of residence times as well as a significant combined role for photo-and biological degradation along the flow path in Arctic watersheds (Cory et al, 2007(Cory et al, , 2013Merck et al, 2012;Laurion and Mladenov, 2013). These previous results show that the photochemical "pretreatment" of stream DOM that occurs during export into lakes and coastal zones may impact the ability of microorganisms to mineralize DOM.…”
Section: Biogeosciencesmentioning
confidence: 72%
See 2 more Smart Citations
“…Previous studies in the Arctic underscore the importance of residence times as well as a significant combined role for photo-and biological degradation along the flow path in Arctic watersheds (Cory et al, 2007(Cory et al, , 2013Merck et al, 2012;Laurion and Mladenov, 2013). These previous results show that the photochemical "pretreatment" of stream DOM that occurs during export into lakes and coastal zones may impact the ability of microorganisms to mineralize DOM.…”
Section: Biogeosciencesmentioning
confidence: 72%
“…Further downstream in larger tributary and Kolyma mainstem waters, it has been shown that lower total amounts of bioavailable DOC is supported almost entirely from predominantly modern radiocarbon aged surface soils and vegetation sources . Aquatic microorganisms may therefore be readily acclimating to significant shifts in DOM composition caused by selective losses of unique DOM fractions (e.g., Kaplan and Bott, 1983;Spencer et al, 2015) alongside high internal demand for labile DOM by stream communities in lower-order streams, which would otherwise generally be expected to result in decreased DOM lability with increasing water residence time (Stepanauskas et al, 1999a, b;Wikner et al, 1999;Langenheder et al, 2003;Sondergaard et al, 2003;Fellman et al, 2010Fellman et al, , 2014.…”
Section: Biogeosciencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible reasons for the observed overall functional equivalence of both communities in both incubation environments, respectively, could be, for example, that the salinity differences between the samples were not high enough to significantly stress the communities (0 vs 4.5 psu). However, it has previously been shown that similar 'mild' salinity differences can affect microbial communities both in terms of function and composition (for example, Langenheder et al, 2003). Another possibility could therefore be that the rock pool communities were already 'pre-conditioned' to environmental fluctuations, as they regularly experience quite drastic differences in environmental conditions (Jocque et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…On a larger scale, spatial differences -water depth for an example -and seasonal changes can also be factors that shift structures of bacterial communities [2,16]. Among those factors affecting bacterial community structures, the salinity gradient is a factor of dramatic impact within aquatic environments [9]. Compared to factors such as temperature, pH or nutrition which may change inconsistently by seasonal shift, pollution or any diverse activity that may modify conditions of aquatic environments, salinity is a definite factor that continuously increases upstream as freshwater streams flow toward the open ocean.…”
Section: Introductionmentioning
confidence: 99%